2021
DOI: 10.1371/journal.pone.0250056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating competition for forage plants between honey bees and wild bees in Denmark

Abstract: A recurrent concern in nature conservation is the potential competition for forage plants between wild bees and managed honey bees. Specifically, that the highly sophisticated system of recruitment and large perennial colonies of honey bees quickly exhaust forage resources leading to the local extirpation of wild bees. However, different species of bees show different preferences for forage plants. We here summarize known forage plants for honey bees and wild bee species at national scale in Denmark. Our focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…via shared floral resources 16 , 39 , 42 , 54 , 55 . Even though some solitary bee species are dietary specialists, visiting flowers of only a few plant species, the presence of generalist species such as honey bees connect many species in one network module, increasing the likelihood of viral transmission to all bee species present in the same environment 56 60 . However, we found that the relation between viral prevalence in honey bees and wild bees differs between viruses.…”
Section: Discussionmentioning
confidence: 99%
“…via shared floral resources 16 , 39 , 42 , 54 , 55 . Even though some solitary bee species are dietary specialists, visiting flowers of only a few plant species, the presence of generalist species such as honey bees connect many species in one network module, increasing the likelihood of viral transmission to all bee species present in the same environment 56 60 . However, we found that the relation between viral prevalence in honey bees and wild bees differs between viruses.…”
Section: Discussionmentioning
confidence: 99%
“…For plants we used the site abundance since we expected a high correlation of bee visitations with plant abundance. Because our aim was not to identify functional traits that determine bee–flower interactions, but to account for floral associations of bees in our models, we assembled a binary network of 207 bee species and 61 plant family interactions based on existing information from interaction records sampled at a greater temporal and spatial extent than our study area (Rasmussen et al., 2021; Wood et al., 2021). This approach provided a more inclusive measure of host plants of bees, closer to the fundamental niche, than what would be achieved from a single survey, such as ours.…”
Section: Methodsmentioning
confidence: 99%
“…This is a notable number of taxa, given the temporally limited sampling undertaken herein, with pollen traps activated < 12 h at the single sampling event in August, in Denmark, and at any of the three sampling events in September, in Austria. Yet, this level of richness is supported by reports that honey bees tend to collect greater diversity of pollen later in the season, to compensate for lower availability of mass-blooming sources (Danner et al, 2017;Rasmussen et al, 2021). Despite the high number of visited plants, most pollen was collected from only three species in Austria and four in Denmark, which accounted for 60.2% (14.0) and 54.6% (9.1) of the total abundance in the former and latter country, respectively (median calculated over all samples; Online Resource 8).…”
Section: Comparing Pollen Preservation Methods By Its2 Metabarcodingmentioning
confidence: 94%